Optimising the adsorption characteristics of spent coffee grounds by thermal and chemical activation - Moroz, Iryna (Lutsk : LNTU, 2025)
The aim of this study was to optimise the adsorption parameters of methylene blue on spent coffee grounds by combining thermal exposure and orthophosphoric acid treatment. The study was carried out using a spectrophotometric method, infrared spectroscopy, and a method for determining the specific surface area by water vapour adsorption. A possible mechanism for the adsorption of the cationic dye methylene blue on coffee grounds has been proposed. It was found that an increase in the processing temperature wasn’t led to a linear increase in the specific surface area and adsorption characteristics of spent coffee grounds. It was discovered that coffee grounds’ adsorption properties were inferior to those of untreated samples at temperatures of 400°C and 800°C. However, thermal activation of spent coffee grounds at 600°C led to a 72% increase in the specific surface area (from 561 to 958 m²/g). Treatment of the waste with 60% orthophosphoric acid solution increased the specific surface area by 23% (up to 690 m²/g) compared to untreated coffee grounds. The most effective in terms of adsorption characteristics of the adsorbent was the combined treatment of coffee grounds with orthophosphoric acid followed by thermal activation at 200°C, which provided a maximum specific surface area of 1078 m²/g and water vapour adsorption of 0.543 g of water per 1 g of sample, exceeding the characteristics of some commercial activated carbon samples. Under these conditions, the highest removal efficiency of methylene blue from model solutions was achieved – 57% in 30 min and almost 90% of the dye in 180 minutes of contact. The proposed conditions for the modification of spent coffee grounds make it possible to obtain an effective biosorbent for wastewater treatment from organic dyes, which is of practical importance for solving environmental problems in the textile and printing industries and the rational use of coffee production waste.
Keywords: biosorbent; coffee waste; thermal modification; phosphate activation; methylene blue